(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the pedagogical foundations for the formation of musical and artistic taste among students of music and art schools. The study analyzes the concept of artistic taste, its stages of development, and the role of aesthetic education in the process of music teaching. Particular attention is paid to the perception of musical works, students’ creative activities, and the application of effective pedagogical approaches. The significance of modern pedagogical technologies and methods in developing artistic thinking and aesthetic values is substantiated.